Evaluation of Readability and Content of Patient Information Texts on Turkish Websites about Pediatric Dentistry Under Sedation - Tuğçe Nur Şahin; Elif Esra Özmen (Ankara University, 2023)
Aim: Disability status, fear, and anxiety can pose an obstacle to the planned dental treatment in children. In such cases, the delivery of dental treatment with sedation is a very common treatment method and more comfortable for both pediatric patients and physicians. This study aims to evaluate the readability and content of patient information texts on websites related to the delivery of dental treatments with sedation in pediatric patients. Material and Methods: The first 60 Turkish websites were scanned in Google (Google LLC, MountainView, California, USA) search using the keywords "pediatric dental treatment with sedation". The patient information texts in 31 websites meeting the inclusion criteria were evaluated according to the Ateşman Readability Index (ARI) and their contents were also examined in terms of whether or not providing sufficient information about the procedure. Results: The texts examined in the study were moderately difficult (52.9±9.4) according to the ARI and at Grade 11-12 level, most of the websites examined were owned by private clinics (64.5%) and the texts were prepared by pedodontists. The content of information on the examined websites could be deemed sufficient in terms of definition of sedation (100%), the indications (100%) and the benefits (83.8%); however, the complications (29.1%), possible procedure-related complications (16.2%), its difference from general anesthesia (54.8%) and the cost (29.1%) were not addressed sufficiently. Conclusion: The results of the study suggested that the relevant patient information texts on Turkish websites need to be organized in a more understandable manner. For this purpose, readability tests may be used before publishing the text. The reason why most of the texts did not mention contraindications, complications, and cost of sedation may be intending not to create fear or prejudice about the procedure among readers. However, when preparing an information text on an interventional medical procedure, it is legally and ethically required to inform the reader about that procedure fully and clearly.